فاعلية تطوير تحمل القدرة باستخدام أسلوب الغمر في الماء والتبريد العضلي علي بعض المتغيرات البدنية والنفسية والمستوي الرقمي لمتسابقي 400م عدو - حسانين، إلهام أحمد (جامعة المنيا - كلية التربية الرياضية, 2019)
يهدف البحث إلي التعرف على فاعلية تطوير تحمل القدرة باستخدام أسلوب الغمر في الماء والتبريد العضلي علي بعض المتغيرات البدنية والنفسية والمستوي الرقمي لمتسابقي 400م عدو، واستخدمت الباحثة المنهج التجريبي باستخدام التصميم التجريبي لمجموعتين إحداهما تجريبية والأخرى ضابطة علي عينة قوامها (٢٨) طالبة من مجتمع طالبات الفرقة الأولي بكلية التربية الرياضية جامعة الوادي الجديد للعام الجامعي ٢٠١٨/٢٠١٩م، وتوصلت نتائج الدراسة على الفاعلية الإيجابية لتدريبات تحمل القدرة باستخدام أسلوب الغمر في الماء والتبريد العضلي في تنمية وتطوير القدرات البدنية لمتسابقي 400م/عدو (عينة البحث) والتي تسهم في تحسين الحالة النفسية والمستوي الرقمي لديهم، زيادة مستوي تحمل القدرة العضلية ساهم بشكل كبير في تطوير مستويات القوة العضلية والقدرة العضلية، هناك علاقة بين القدرات البدنية الممثلة لتحمل القدرة وتحسن الحالة النفسية ومستوي الإنجاز الرقمي لمتسابقي 400م/عدو، وتوصي الباحثة بضرورة الاهتمام بتنمية وتطوير تحمل القدرة وضرورة احتواء برامج التدريب الخاصة بالأنشطة الرياضية التي تتطلب القدرة العضلية علي تدريبات تهدف إلى تنمية تحمل القدرة العضلية، والاهتمام باستخدام أسلوب الغمر في الماء والتبريد العضلي في تنمية اللياقة البدنية والنفسية والإنجاز الرقمي لمتسابقي مسابقات الميدان والمضمار بصفة خاصة وفي الرياضات المختلفة بصفة عامة، محاولة لفت نظر المدربين والباحثين إلي ضرورة التعرف علي أهمية تناول تحمل القدرة باستخدام أسلوب الغمر في الماء والتبريد العضلي بالمزيد من المراجع والأبحاث العلمية. The research aims at recognizing the effectiveness of developing capacity endurance by using the method of flooding in water and muscular cooling on some physical, psychological variables and record level for 400m.running competitors. The researcher used the experimental method by using the experimental design for two groups, one is an experimental group and the other is a control group on a sample of (28) first female graders at faculty of physical education – New Valley university on university year 2018/2019. The findings of the study found the positive effectiveness of capacity endurance exercises by using the method of flooding in water and muscular cooling in developing physical capacities for 400m. running competitors (the research sample) that contributes in improving their psychological state and record level. Increasing the level of muscular capacity endurance contributes greatly in developing the levels of muscular power and muscular capacity and there is a relationship between physical capacities representative of the capacity endurance, improving psychological state and the level of record achievement for 400m.running competitors. The researcher recommends the necessity of developing the capacity endurance and the necessity that the training programs of sport activities requiring the muscular capacity should include exercises aiming at developing the muscular capacity endurance, interested in using the method of flooding in water and muscular cooling in developing physical and psychological fitness and record achievement for field and track competitors in particular and different sports in general, the trial to pay the attention of trainers and researchers to the necessity of recognizing the importance of dealing the capacity endurance by using the method of flooding in water and muscular cooling with further references and scientific researches."
Keywords: التبريد العضلي -- المتغيرات النفسية -- القدرات البدنية